Exploring game ideas for stresslessness in the automotive domain - Krome, S.; Walz, Steffen; Greuter, S.; Holopainen, J.; Gerlicher, A.; Schleehauf, M. (2014)
In this paper we report on the results of a series of ideation workshops with the goal to explore game designs that promote stresslessness and wellbeing in the automotive context. We present two parts that are particular interesting for further research. First, we provide an overview of our preliminary work on a catalog of design items for gameful stresslessness in the car. Second, we report on a selection of the game ideas created during the ideation workshops and discuss the findings regarding directions for further research.